Molecular Diversity Analysis of Some Selected Brri Developed Rice Varieties Using Ssr Markers - Islam, M Z; Siddique, M A; Prince, MFRK; Rashid, ESMH; Khalequzzaman, M (SAARC Journal of Agriculture, 2023)
Molecular characterization of 26 modern rice varieties of Bangladesh was performed using 52 simple sequence repeat markers (SSRs) to estimate the genetic diversity and to reveal genetic relationships among rice cultivars. A total of 156 alleles were detected where the number of alleles per locus generated by each marker varied from 2 to 7, with an average of 3. The band size for a given microsatellite locus ranged from 79 to 278 bp. The polymorphism information content (PIC) for the SSR loci ranged from 0.08 to 0.79, with an average of 0.35. RM566 was the best marker for identification and variability assessment of varieties as revealed by PIC values. A UPGMA dendrogram generated using the NTSYS-pc revealed four clusters with a similarity coefficient of 0.55, whereas phylogenetic cluster analysis of the SSR data based on Nei-genetic distance divided the varieties into three groups. Two- and three-dimensional graphical views of principal coordinate analysis showed the spatial distribution of the varieties and revealed that BRRI dhan56, BRRI dhan51, BRRI dhan52, BRRI dhan61, BRRI dhan62 and BRRI dhan66 were found far away from the centroid of the cluster. The findings of this study are helpful for varietal identification, background selection during backcross breeding and for selecting the suitable genetically diverse parents for crossing programs. SAARC J. Agric., 21(2): 1-14 (2023)